Workplace health promotion and labour market performance of employees - Martin Huber; Michael Lechner; Conny Wunsch (University of Basel, Center of Business and Economics (WWZ), 2014)
This paper investigates the average effects of (firm-provided) workplace health promotion measures in form of the analysis of sickness absenteeism and health circles/courses on labour market outcomes of the firms' employees. Exploiting linked employer-employee panel data that consist of rich survey-based and administrative information on firms, workers and regions, we apply a flexible propensity score matching approach that controls for selection on observables as well as on time-constant unobserved factors. While the effects of analysing sickness absenteeism appear to be rather limited, our results suggest that health circles/courses increase tenure and decrease the number of job changes across various age groups. A key finding is that health circles/courses strengthen the labour force attachment of elderly employees (51-60), implying potential cost savings for public transfer schemes such as unemployment or early retirement benefits.
Keywords: I10; I19; J32; 330; Firm health policies; health circles; health courses; analysis of sickness absenteeism; matching